Rockwood & Wilkins' fractures in children - Flynn, John M.; Skaggs, David L.; Waters, Peter M. (Lippincott Williams & Wilkins, 2015)
Presents complete coverage of all types of children's fractures. This book is suitable for pediatric orthopedic surgeons and orthopedic residents. It features a coverage of pain medicine and casting. It also offers guidance on numerous operative and management techniques.